RELASI SOSIAL ANTARA ORANG TUA ASUH DENGAN ANAK TELANTAR DI PANTI SOSIAL: SOCIAL RELATION BETWEEN CAREGIVER PARENTS WITH HOMELESS CHILDREN IN SOCIAL HOME - Alfemoran, M. Rizki; Fadzlul, Fadzlul (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
ABSTRACT Introduction Homeless child experience conditions that make it difficult for a child to fulfill their rights and needs, the government provides social welfare services for homeless child so that they are guided by foster parents in carrying out temporary alternative care. Therefore, it is important to deepen the social relations that occur between foster parents and homeless child. Method This research is qualitative phenomenology, using data collection techniques of unstructured interviews, observation, and document study with Interpretative Phenomenological Analysis (IPA) data analysis. There were 4 research participants, namely: two foster parents and two homeless child. Result The research results show the description of social relations, namely: helping each other, closeness, communication, togetherness, guidance and instruction, feedback, receiving benefit, conflict resolution, affection feeling, and collegial relationships which are classified into the types of social relations communal sharing, authority ranking and equality matching. The factors that influence social relations are work systems, first impressions, individual’s characteristics, negative behavior, the feelings of sympathy and empathy. Keywords: Social relation, social home, caregiver parent ABSTRAK Pendahuluan Anak telantar mengalami kondisi yang sulit bagi seorang anak untuk memenuhi hak dan kebutuhannya, pemerintah menyelenggarakan layanan kesejahteraan sosial untuk anak telantar agar dibimbing oleh orang tua asuh dalam melakukan pengasuhan alternatif sementara. Maka dari itu, penting untuk melakukan pendalaman tentang relasi sosial yang terjadi antara orang tua asuh dengan anak telantar. Metode Penelitian ini adalah kualitatif fenomenologi, menggunakan teknik pengumpulan data wawancara tidak terstruktur, observasi, dan studi dokumen dengan analisis data Interpretative Phenomenological Analysis (IPA). Partisipan penelitian sejumlah 4 orang, yaitu: 2 orang tua asuh dan 2 anak telantar. Hasil penelitian menunjukkan gambaran relasi sosial, yakni: tolong menolong, kedekatan, komunikasi, kebersamaan, bimbingan dan arahan, umpan balik, menerima manfaat, penyelesaian konflik, rasa afeksi, dan hubungan kolegal yang terklasifikasi pada jenis relasi sosial communal sharing, authority ranking dan equality matching. Adapun faktor yang mempengaruhi relasi sosial tersebut adalah sistem kerja, impresi pertama, karakteristik individu, perilaku negatif, rasa simpati dan empati. Kata Kunci : Relasi sosial, panti sosial, orang tua asuh